THE MEANINGFUL OF LIFE OF PRIEST - Charlys Charlys; Ni Made Taganing Kurniati (Jurnal Psikologi, 2006)
The aim of this study is to gain the understanding about the processes of being a priest andfinding his meaningful of life in the promise to Lord in poverty, purity and obidience inchurch. Process of meaningful of life such as meaninglessm self-acceptance, finding the lifemeaning, meaning realization and meaningful of life. This study is using case study forgaining the data. The participants if this study is a 40 years old priest and already do thepromise to the Lord in 13 years. He heas been started the promise since 1982 and decided topromise for his whole life in 1994. The results shows that he found the meaningful of life inthe church.